2021
DOI: 10.3390/pharmaceutics13020216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Protein Adsorption on the Distribution and Retention of Intratumorally Administered Gold Nanoparticles

Abstract: The heterogeneous distribution of delivery or treatment modalities within the tumor mass is a crucial limiting factor for a vast range of theranostic applications. Understanding the interactions between a nanomaterial and the tumor microenvironment will help to overcome challenges associated with tumor heterogeneity, as well as the clinical translation of nanotheranostic materials. This study aims to evaluate the influence of protein surface adsorption on gold nanoparticle (GNP) biodistribution using high-reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 74 publications
(86 reference statements)
1
22
0
Order By: Relevance
“…In previous studies, we demonstrate that GNP cellular uptake [20,21], as well as intratumoral distribution and retention [22,23], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [22]. BSA modification shields the metal core and prevents unwanted non-specific adsorption of other agents onto the particles.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In previous studies, we demonstrate that GNP cellular uptake [20,21], as well as intratumoral distribution and retention [22,23], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [22]. BSA modification shields the metal core and prevents unwanted non-specific adsorption of other agents onto the particles.…”
Section: Introductionmentioning
confidence: 83%
“…Evaluating the tumoral distribution of a drug or particle-drug conjugate is an important variable that is often neglected, as most drugs are assumed to distribute homogeneously into a tumor [19]. In previous studies, we demonstrate that GNP cellular uptake [20,21], as well as intratumoral distribution and retention [22,23], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [22].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…To date, iodine is the most commonly used CT contrast agent to enhance contrast resolution in the body, but it results in short blood circulation time and rapid clearance from the kidneys [28]. Several studies demonstrated that gold nanoparticles have prolonged circulation times dependent on their surface chemistry, such that the particles can achieve a CT outcome with good efficiency with retention times in the body longer than other standard contrast agents [29][30][31]. Additionally, gold nanoparticles of different sizes are able to enhance the effects of radiation [32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, iodine is the most commonly used CT contrast agent to enhance contrast resolution in the body tissues, but it results in short blood circulation time and rapid clearance from the kidneys [28]. Several studies demonstrated that gold nanoparticles have prolonged circulation times dependent on their surface chemistry, such that the particles can achieve a CT outcome with good efficiency with retention times in the body longer than other standard contrast agents [29][30][31]. Additionally, gold nanoparticles of different sizes are able to enhance the effects of radiation.…”
Section: Introductionmentioning
confidence: 99%